Developing economies and international investors. Do investment promotion agencies bring them together? - Torfinn Harding; Beata Smarzynska Javorcik (Statistics Norway, Research Department, 2007)
Many countries spend significant resources on investment promotion agencies (IPAs) in the hope of attracting inflows of foreign direct investment (FDI). Despite the importance of this question for public policy choices, little is known about the effectiveness of investment promotion efforts. This study uses newly collected data on national IPAs in 109 countries to examine the effects of investment promotion on FDI inflows. The empirical analysis follows two approaches. First, we test whether sectors explicitly targeted by IPAs receive more FDI in the post-targeting period relative to the pre-targeting period and non-targeted sectors. Second, we examine whether the existence of an IPA is correlated with higher FDI inflows. Results from both approaches point to the same conclusion. Investment promotion efforts appear to increase FDI inflows to developing countries. Moreover, agency characteristics, such as its legal status and reporting structure, affect the effectiveness of investment promotion. There is also evidence of FDI diversion due to investment incentives offered by other countries in the same geographic region.
Keywords: F21; F23; O1; 330; foreign direct investment; investment promotion; investment incentives